PERAN PROFETIK ADAM DALAM MERINTIS PERADABAN MANUSIA - Putri Hafizatul Aini; Iffah Azzahro (EL-ADABI : Jurnal Studi Islam, 2024)
This study presents a summary of the history of the creation of Prophet Adam and its impact on the foundation of human civilization. It also explores the role of Adam as the first human being based on the Qur’an and Hadith. By examining Qur’anic verses mentioning Adam and their interpretations, this research strengthens the understanding of Adam as the first caliph on earth. The study is presented descriptively and analytically, using data collected through library research from books, tafsir works, and journals relevant to the subject. The findings reveal that the Qur’an and Hadith depict Prophet Adam a prophetic pioneer who initiated human civilization. The prophetic experience of Adam confirms that Allah created the universe to support faithful humans in fulfilling the duties of caliphate. Despite human weaknesses and susceptibility to temptation, they are endowed with the ability to choose the path of obedience to Allah. Furthermore, the study emphasizes the importance of avoiding greed and envy, and fulfilling the responsibilities of caliphate by promoting justice, peace and harmony on earth.